Imitating the Devil: Cyprian on Jealousy and Envy - Murphy, Edwina 1970- (2018)
If imitating Christ in his humility leads to peace and unity, imitating the devil in his jealousy leads to conflict and self-destruction. So warns Cyprian of Carthage in De zelo et livore, where he identifies the devil as the originator of envy, precipitating humanity’s downfall as well as his own. Cyprian further illustrates these fatal effects by pairing exemplars of jealousy with their innocent victims. Cyprian’s use of these models demonstrates the importance of this reading strategy for his exegesis and the value he ascribes to imitation in Christian formation. Furthermore, whilst Cyprian’s emphasis on unity is well known, this study highlights that it is not achieved simply by avoiding schism. Rather, structural concerns are just one expression of Cyprian’s conviction that conflict and division are vices rooted in the flesh. Those who claim to be Christians must, like Christ, live according to the Spirit in love and peace.
Keywords: Biblical Interpretation -- patristic exegesis -- reception of Scripture